Attitudes of Non-Disabled Pupils towards Disabled Pupils to Promote Inclusion in the Physical Education Classroom - Delgado-Gil, Serafín; Mendoza-Muñoz, David Manuel; Galán-Arroyo, Carmen; Denche-Zamorano, Ángel; Adsuar, Jose Carmelo; Mañanas-Iglesias, Carlos; Castillo-Paredes, Antonio; Rojo-Ramos, Jorge (Children, 2023)
Inclusive education for disabled people is becoming increasingly important globally. Improving the factors that support the inclusion of people with disabilities in education is one of the main objectives. In addition to teachers, another major factor is how the attitudes of students without disabilities affect those with disabilities, which should be considered in maintaining an inclusive classroom climate. The aim of the study was to analyse the attitudes of non-disabled students towards the inclusion disabled students in Physical Education (PE) and to investigate differences according to gender and school location. A total of 805 girls and boys participating in PE in public secondary schools (12–18 years old) in Extremadura were analysed through the AISDPE (Attitudes towards the Inclusion of Students with Disabilities in PE) questionnaire. The results show students without disabilities have positive attitudes towards the inclusion of students with disabilities. The majority were female. No significant differences were found regarding the location of the school. There are positive attitudes towards the inclusion of students with disabilities in the PE classroom, but these could be improved, especially in aspects more related to cognitive factors. For this, it is necessary for teachers to provide their students with the necessary tools and knowledge to better understand the possibilities and difficulties presented to students with disabilities, thus promoting a more inclusive classroom.